Peranan Organisasi Aisyiah Daerah Kota Surakarta dalam Pemberdayaan Perempuan Masa Pra Kemerdekaan (1923-1945) - Mahmudah, Annisa Jamilatul (UIN Raden Mas Said Surakarta, 2020)
This study is about the history of women at the local level, the Surakarta branch of the Aisyiyah organization in empowering women before independence day in 1923-1945. This study uses a historical methodology which has four main stages of the historical method, there are (1) heuristics, (2) source criticism, (3) interpretation, and (4) historiography. The results of this study indicate that the Surakarta branch of the Aisyiyah organization made a real contribution through programs and activities in empowering women that were formed in 1923-1945. These programs include, in the field of religion, such as holding recitations, worship facilities and infrastructure by establishing a prayer room for women, and education such as Bustanul Atfal (for early childhood), Huishoud School (Girls clever School), Nasyiatul Aisyiyah School (Elementary School). ), Praja students, besides that there is also a reading course as a movement for women's literacy.